Animal models for exploring the pharmacokinetics of breast cancer therapies - Rashid, Omar M. (Expert Opin Drug Metab Toxicol, 2014)
INTRODUCTION: Despite massive expenditures in research and development to cure breast cancer, few agents that pass preclinical trials demonstrate efficacy in humans. Although this endeavor relies on murine models to screen for efficacy before progressing to clinical trials, historically there has been little focus on the validation of these models, even in the era of targeted therapy where understanding the genetic signatures of tumors under study is critical. AREAS COVERED: This review includes the transgenic, xenograft, and syngeneic murine breast cancer models, the ectopic, orthotopic and intravenous methods of cell implantation, and the ethics of animal experimentation. It also includes the latest data on tumor gene expression and the issues to consider when exploring the pharmacokinetics and efficacy of breast cancer therapies. EXPERT OPINION: Breast cancer drug development is expensive and inefficient without a consensus preclinical murine model. Investigators must approach the choice of murine model with the same sophistication that is applied to the choice of in vitro assays to improve efficiency. Understanding the limitations of each model available, including the nuances of tumor gene signatures, is critical for investigators exploring the phamacokinetics and efficacy of breast cancer therapies, especially in the context of gene profiling and individualized targeted therapy.